Debate: Limitations on universality: the "right to health" and the necessity of legal nationality - Morley Christopher P; Cohen Elizabeth F; Kingston Lindsey N (BMC, 2010)
Abstract Background The "right to health," including access to basic healthcare, has been recognized as a universal human right through a number of international agreements. Attempts to protect this ideal, however, have relied on states as the guarantor of rights and have subsequently ignored stateless individuals, or those lacking legal nationality in any nation-state. While a legal nationality alone is not sufficient to guarantee that a right to healthcare is accessible, an absence of any legal nationality is almost certainly an obstacle in most cases. There are millions of so-called stateless individuals around the globe who are, in effect, denied medical citizenship in their countries of residence. A central motivating factor for this essay is the fact that statelessness as a concept is largely absent from the medical literature. The goal for this discussion, therefore, is primarily to illustrate the need for further monitoring of health access issues by the medical community, and for a great deal more research into the effects of statelessness upon access to healthcare. This is important both as a theoretical issue, in light of the recognition by many of healthcare as a universal right, as well as an empirical fact that requires further exploration and amelioration. Discussion Most discussions of the human right to health assume that every human being has legal nationality, but in reality there are at least 11 to 12 million stateless individuals worldwide who are often unable to access basic healthcare. The examples of the Roma in Europe, the hill tribes of Thailand, and many Palestinians in Israel highlight the negative health impacts associated with statelessness. Summary Stateless individuals often face an inability to access the most basic healthcare, much less the "highest attainable standard of health" outlined by international agreements. Rather than presuming nationality, statelessness must be recognized by the medical community. Additionally, it is imperative that stateless populations be recognized, the health of these populations be tracked, and more research conducted to further elaborate upon the connection between statelessness and access to healthcare services, and hence a universal right to health.